1991
DOI: 10.1002/1097-0142(19910501)67:9<2227::aid-cncr2820670903>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of age on treatment choice and survival in elderly breast cancer patients

Abstract: To investigate the effect of age on treatment choice and survival in patients with breast cancer, data from the cancer registry of the Netherlands Cancer Institute (NKI, Amsterdam, The Netherlands) on 611 women have been analyzed. All patients 55 years and older admitted to the NKI for primary treatment of breast cancer between 1981 and 1986 were selected. For women 75 years and older, physicians were less likely to use treatment of adjuvant radiation therapy after a mastectomy and more often employed primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(33 citation statements)
references
References 8 publications
2
31
0
Order By: Relevance
“…[5][6][7] Although little is known about the pathology and biology of breast cancer in older patients, many clinical trials have shown that women who develop breast cancer at an elderly age have less aggressive disease and decreased risk of recurrence. [8][9][10][11] In contrast, a few studies have demonstrated that in postmenopausal patients with hormone receptor-positive breast cancer, increasing age is associated with higher disease-specific mortality.…”
supporting
confidence: 83%
“…[5][6][7] Although little is known about the pathology and biology of breast cancer in older patients, many clinical trials have shown that women who develop breast cancer at an elderly age have less aggressive disease and decreased risk of recurrence. [8][9][10][11] In contrast, a few studies have demonstrated that in postmenopausal patients with hormone receptor-positive breast cancer, increasing age is associated with higher disease-specific mortality.…”
supporting
confidence: 83%
“…7 Several studies showed that younger patients had better survival than older patients, 6 -11 and this difference in survival between age groups does not seem to be the result of the difference of treatment but suggests the influence of age-related factors such as comorbid conditions that place the older group at greater risk of poor prognosis on the course of metastatic disease. 6 In agreement with previous studies, 9,10,13,16 this study demonstrated that comorbid conditions increased with age (hypertension: OR, 4.66; 95% CI, 3.11-6.99; CCS: OR, 2.59; 95% CI, 1.58 -4.24; hCCS: OR, 3.94; 95% CI, 2.73-5.69). Hypertension was the most prevalent comorbid condition among breast cancer patients 9,10,12,13,16,19,37 and was more likely to be found in older patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have shown that WBRT can worsen performance status 2 . Quality of life (QOL) and performance status may be very important in older patients as the aging process can lead older patients to have a lower tolerance to aggressive therapies and less functional reserve to help them recover from clinical decline [8][9][10] . WBRT has also been associated with higher risk of chronic neurotoxicity especially in the older patient population 5,6 .…”
Section: Introductionmentioning
confidence: 99%